Factors affecting farmer's adoption of disease - Free mother stock of strawberry in Borkeaw Sub - District, Samoeng District, Chiang Mai Province - Wet Techa (2018)
The objectives of this research were to investigate relationships between characteristics and socio - economic factors influencing farmers' adoption of disease-free mother stock of strawberry, and to identify problems, obstacles and needs of farmers on strawberry disease-free mother stock in Borkeaw Sub-district, Samoeng District, Chiang Mai Province. Population was farmers who grew strawberries in Borkeaw Sub-district, Samoeng District, Chiang Mai Province. It was found that most of strawberry growers were 41 years old and elementary school graduates. The growers had 4 years of growing experience. Average income of farmers was approximately 99,625 Baht per year. Each farmer held 2.81 rais of land in average with 2.78 rais for strawberry planting. Average family labors were 2. The farmers received information through meetings, study tour and training. Most growers grew Praradchatan 20 variety and sold their product through traders. Most of the farmers had no contact with agricultural extension officers. The hypothesis testing showed that factors related to farmers' adoption of disease-free mother stock of strawberry were famers' level of education, total family income, the size of land cultivation and information perceived. Major problems of strawberry growers were unhealthy planting stocks. Other problems were diseases and pests, low product price and inadequate knowledge of the farmers. Suggestions were proposed, involving supports in providing marketing information of strawberry. Government officials should conduct planting promotion as well as an transferring the knowledge on disease and pest control. Strawberry trading center should also be considered.